38 VERIFIABLE DONOR DEATHS IN LIVING DONOR LIVER TRANSPLANTATION. (1st March 2006) - Kenison, J. R.; Adam, P.; Lo, C. M.; Trotter, J. F.
Abstract : Background: In living donor liver transplantation (LDLT) the hepatic lobe donor incurs a measurable risk, the most important of which is death. The actual risk of death following a donor hepatectomy is unknown because of the absence of a sufficiently large database to allow an accurate determination of this infrequent but devastating outcome. In the absence of a definitive estimate of the risk of donor death, the medical literature has become replete with anecdotal reports of donor deaths, which in many cases are based on verbal reports, circularly referenced or unsubstantiated. Because donor death is one of the most important outcomes of LDLT, we performed a comprehensive survey of the medical and lay literature to provide a referenced source of worldwide donor deaths. Methods: We reviewed all published articles available from PubMed and from the lay literature (using <www.google.com > and <http://www.refdesk.com/paper.html >), which reported donor outcomes from 1989 to October 2005. We classified each death as definitely, possibly, or unlikely related to donor surgery. Results: There were a total of 16 deaths in living liver donors reported in the medical and lay literature, as shown in the Table . Ten were "definitely, " two were "possibly, " and three were "unlikely" related to donor surgery. The estimated total number of LDLT's performed in the United States is 2, 000 and worldwide is 4, 800. The estimated rate of donor death definitely related to donor surgery is 3/2, 000 or 0.15% in the United States and 11/4, 800 or 0.229% worldwide. The rate of donor death that is definitely or possibly related to the donor surgery is 5/2, 000 or 0.25% in the United States and 14/4, 800 or 0.292% worldwide. Conclusion: The purpose of this analysis is (1) to provide a referenced source document of living donor deaths published in the medical and/or lay literature, (2) to provide a better estimate of donor death rate associated with this procedure, and (3) to provide an impetus for centers with unreported deaths to submit these outcomes to the liver transplantation community.